2015
DOI: 10.1007/s00405-015-3554-4
|View full text |Cite
|
Sign up to set email alerts
|

The relation between childhood obesity and adenotonsillar hypertrophy

Abstract: Childhood obesity is a common and significant public health problem all over the world. As a well-known fact obese children have an increased risk of obesity-associated comorbidities, including obstructive sleep apnea, diabetes, and cardiovascular disorders at an earlier age compared to their normal weight peers. They also have an increased risk of poor self-esteem, greater body dissatisfaction, and increased peer teasing that lead to a lower health-related quality of life. While the presence of adenoid hypert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 36 publications
3
19
0
3
Order By: Relevance
“…They were lighter and had a lower BMI compared with controls. Some studies have reported higher weights and higher BMI's in patients with OSA, which might indicate that the reason for OSA in these children was more related to obesity than to adenotonsillar hypertrophy . Others have reported lower age, weight and BMI at the time of surgery in children with OSA, possibly because the children were failing to thrive or the symptoms and signs were being noticed earlier due to their severity .…”
Section: Discussionmentioning
confidence: 99%
“…They were lighter and had a lower BMI compared with controls. Some studies have reported higher weights and higher BMI's in patients with OSA, which might indicate that the reason for OSA in these children was more related to obesity than to adenotonsillar hypertrophy . Others have reported lower age, weight and BMI at the time of surgery in children with OSA, possibly because the children were failing to thrive or the symptoms and signs were being noticed earlier due to their severity .…”
Section: Discussionmentioning
confidence: 99%
“…Adenotonsillar hypertrophy and obesity are the important predictors of OSA among children, and most of the time they are coexistent. [24] In addition to mimicking ADHD, OSA has been found to have multiple metabolic and cardiovascular complications among children. Studies have reported that OSA among children leads to lipid peroxidation; [25] increment of proinflammatory markers in body, for example, interleukin 6, interleukin 18, plasminogen activating factor, high-sensitivity-C reactive protein; [26,27] insulin resistance; [28] endothelial dysfunction; [29] and an increase in blood pressure.…”
Section: Journal Of Neurosciences In Rural Practice ¦ Volume 8 ¦ Issumentioning
confidence: 99%
“…Among the 312 studied patients, 70.2% were male and 29.8% were female. Obviously, in different studies, the proportion of these communities is also different [12], [14], [15], and the reason for this difference is the sampling in different study communities, the population under study, and the male and female populations of different geographic areas. As noted in the findings section, sex was significantly associated with BMI percentile and height.…”
Section: Discussionmentioning
confidence: 99%